Impact of Increased Enoxaparin Dosing on Anti-Xa Levels for Venous Thromboembolism Prophylaxis in Trauma Patients. Issue 9 (September 2022) - Bellfi, Lillian T.; Zimmerman, S. Anthony; Boudreau, Ryan; Mosier, Willard; Smith, Alison; Rueb, Nicole; Hunt, John P.; Stuke, Lance; Greiffenstein, Patrick; Schoen, Jonathan; Marr, Alan
Introduction: Venous thromboembolism (VTE) contributes to significant morbidity in trauma patients while increasing hospital costs and length of stay. Standard trauma prophylaxis dosing with enoxaparin 30 mg twice daily may be inadequate to prevent VTEs. The objective of this study was to compare standard dosing of enoxaparin to an increased dose of enoxaparin 40 mg twice daily for trauma patients. We hypothesized that increasing thromboprophylaxis dosing leads to an increase in therapeutic anti-Xa levels and reduced VTE rates. Methods: A retrospective study was performed from January 2020 to June 2021 at a Level I trauma center, following implementation of an increased enoxaparin dosing strategy. Patients with increased enoxaparin dosing were compared with those who received standard dosing. The primary outcome evaluated was the incidence of subtherapeutic anti-Xa levels. Secondary outcomes evaluated VTE rates and clinically significant bleed. Results: A total of 204 trauma patients were identified. Ninety-one patients received an increased enoxaparin dose compared to 113 who received standard dosing. The baseline demographics of both groups were similar ( P > .05). Subtherapeutic levels were higher with standard dosing compared to the increased dose (50 vs 22%, P = .003). Higher VTE rates were observed with standard dosing compared to higher dosing (6.2 vs 3.3%) but with a lower incidence of major bleed (1.8 vs 4.4%). Overall annual VTE rates decreased from 1.6 to 1.3% after implementation of the increased dosing regimen. Conclusions: This study demonstrated that an increased dosing strategy decreased rates of subtherapeutic anti-Xa levels and trended toward lower overall VTE rates in trauma.